Corrosion characterization of waste incinerator water-cooled wall material 20G steel under sulfur-chlorine atmosphere - Yincong ZHOU; Xiaohe XIONG; Houzhang TAN (Meitan xuebao)
High temperature corrosion poses a threat for waste incinerators operation, in which corrosive elements S and Cl play an important role in the corrosion process. The H2S and HCl present different physicochemical properties and corrosion characteristics in the reaction with alloys and oxide films. For this end, gas-phase corrosion kinetics experiments were carried out to compare the rate difference between high-temperature H2S corrosion and HCl corrosion, and the corrosion depth model was optimized based on the Pilling-Bedworth theory, which can predict the corrosion depth under different atmospheres. In turn, it can be used to some extent for life cycle calculations of waste incinerator pipe wall materials. The results showed that the corrosion rate of H2S was greater than that of HCl at 450 ℃ and 550 ℃. And the corrosion rate of H2S was greater at the beginning of the reaction at 650 ℃, while the corrosion rate of HCl reversed to exceed the corrosion rate of H2S after 72 h. The corrosion rates of H2S and HCl showed a positive correlation with temperatures. Although the average activation energy of the H2S corrosion reaction was 22.8 kJ/mol, lower than the average activation energy of HCl corrosion reaction 52.0 kJ/mol, the HCl corrosion reaction was more sensitive to the temperature. Thus, as the temperature rose, the corrosion rate of HCl increased significantly faster than the H2S. H2S corrosion rate and concentration showed a positive correlation while HCl corrosion rate showed no positive correlation with HCl concentration. Moreover, oxygen has a synergistic effect on the corrosion rate of H2S and HCl. In the presence of oxygen, the corrosion rate of H2S and HCl was significantly accelerated compared with the absence of oxygen, and the corrosion rate increase was 52.5% on average. H2S and HCl mainly penetrated into the iron matrix by pitting corrosion, resulting in the main component of the sample surface was iron oxide, and the corrosion products of H2S and HCl was FeS and FeClx, respectively.